Liquidity Banking and Its Impact on the Return and Risk: Applied Research in the Rasheed Bank (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to measure and analyze the reality of liquidity in the Rasheed Bank and determine their impact on risk and return in order to identify the extent of the efficiency of the management of liquidity by the Bank and how to employ them in a profitable investment areas, and analysis of the compatibility of the liquidity gap and gap the balance sheet (sensitive interest rate) and affected net interest Change prices, and through the adoption of style ladder recommended Meritassets and liabilities by the Central Bank of Iraq, as it is an important and vital aspects in commercial banks' management, when there is a commonly used optimizing the resources of the bank available, it means that there is a banking efficient management is working to stabilize its financial position, So research was focused on the problem of the balance between return and risk in liquidity management, which is a constant challenge and daily problem faced by departments of commercial banks, "including GeneralManagement Rasheed Bank / Management (sample) for the period from 31/1/2013–31/12/2013. Using Some of the financial ratios in Applied Analysis (liquidity ratios, return and liquidity risk), enhanced neo-statistical (SPSS analysis) to prove the strength of the relationship and impact between research, the research found a number of the most important conclusions that there is surplus cash in the bank, and a yield and risk Mtosttin and positive budget gap. The researcher recommends reducing the size of the cash assets, and benefit from the increased deposits and invested in r fled profitable investment.